DED Powder Modification for Single-Layer Coatings on High-Strength Steels - Unai Garate; Enara Mardaras; Jon Arruabarrena; Garikoitz Artola; Aitzol Lamikiz; Luis Norberto López de Lacalle (Journal of Manufacturing and Materials Processing)
In the design of L-DED (laser-directed energy deposition) cladding processes, the chemical composition of the metallic powders is typically assumed to match that of the intended coating. However, during the deposition of the first layer, dilution with the substrate alters the weld metal composition, deviating from the nominal powder chemistry. Although the application of multiple layers can gradually reduce this dilution effect, it introduces additional complexity and processing time. This study proposes an alternative strategy to counteract substrate dilution from the very first deposited layer, eliminating the need for multilayer coatings. Specifically, to achieve a corrosion-resistant monolayer of AISI 316L stainless steel on a high-strength, quenched-and-tempered AISI 4140 steel substrate, a dilution-compensating alloy powder is added to the standard AISI 316L feedstock. Single-layer coatings, both with and without compensation, were evaluated in terms of chemical composition, microstructure, and corrosion resistance. The results show that unmodified coatings suffered a chromium depletion of approximately 2 wt.%, leading to a reduced pitting potential of Ep = 725 ± 6 mV in synthetic seawater. In contrast, the use of the compensation alloy preserved chromium content and significantly improved corrosion resistance, achieving a pitting potential of Ep = 890 ± 9 mV.